Off-pump vs. on-pump bypass surgery grafting in diabetic patients with three-vessel disease: a propensity score matching study - Song, Yu; Wang, Chen; Tang, Chuanbin; Huang, Xiaofan; Wang, Dashuai; Li, Rui; Luo, Jingjing; Tuerxun, Yisilamujiang; Li, Yuanming; Liu, Baoqing; Wu, Long; Du, Xinling (Frontiers in Cardiovascular Medicine, 2023)
Background: Controversy exists regarding theadvantages and risks of off-pump versus on-pump coronary artery bypass grafting (CABG) for patients with diabetes. We therefore compared the early clinical outcomes of off-pump versus on-pump procedures for diabetic patients with three-vessel disease.We conducted a retrospective analysis of clinical data from 548 diabetic patients with three coronary artery disease who underwent isolated CABG from January 2016 to June 2020. To adjust the differences of baseline characteristics between the off-pump CABG(OPCABG) and onpump CABG (ONCABG) groups, propensity score matching was used. Following 1:1 matching, we selected 187 pairs of patients for further comparison of outcomes within the first 30 days after surgery.The preoperative characteristics of the patients between the two groups were clinically comparable after propensity score matching.. The OPCAB group exhibited a significantly higher incidence of incomplete revascularization (27.3% vs 14.4%; P=0.002) compared to the ONCAB group. No differences were seen in mortality within 30-daybetween the matched groups (1.1% vs 3.7%; P=0.174). Notably, the OPCAB group had a lower risk of respiratory failure or infection (2.1% vs 7.0%; P=0.025), less postoperative stroke (1.1% vs 4.8%; P = 0.032), and reduced postoperative ventilator assistance time (35.8±33.7 vs 50.9±64.8; P=0.005). This is a provisional file, not the final typeset article Conclusions: OPCAB in diabetic patients with three-vessel disease is a safe procedure with reduced early stroke and respiratory complications and similar mortality, myocardial infarction, and renal failure requiring dialysis to conventional on-pump revascularization.